Managers at Work - Swamidass, Paul M.
Paul M. Swamidass and M. Dayne Aldridge offer Ten Rules for Timely Task Completion in Cross-Functional Teams. Followed by Bert Thurlings and Koenraad Debackere on Trends in Managing Industrial Innovation.